A prospective observational study of prevalence, incidence, and prognostic implications of right-sided heart failure in acute respiratory distress syndrome patients - Sahu, Chinmay; Rao, K. S.; Mishra, Prasanna; Panda, Rajesh (International Journal of Research in Medical Sciences, 2023)
Background: Acute respiratory distress syndrome (ARDS) is a common reason for respiratory failure in critically unwell patients. Noncardiogenic pulmonary edoema that develops suddenly, acute hypoxemia, and the need for mechanical ventilation are its defining features. This study's major objective was to examine the likelihood of cor-pulmonale in ARDS patients receiving protective ventilation, as well as its prognosis over the long term. Methods: S. C. B. medical college in Odisha, India served as the setting for this prospective observational study. 100 consecutive patients with moderate to severe ARDS were included in the trial in accordance with the Indian criterion. With an average PEEP of 91 cm H2O and a plateau pressure cap of 31 cm H2O, these patients were ventilated. Results: There were 100 patients altogether, 63 males and 37 females, with a mean age of 59-19 years. The interval between the diagnosis of ARDS and TEE was typically 0.75-0.97 days. There were 100 cases of cor pulmonale, which was shown to be common (21.09%). Lung injury occurred more frequently in patients with cor pulmonale compared to other patients when an infectious cause was involved [37 (79.06%) vs. 67 (57.61%)]. Conclusions: The incidence of cor pulmonale in ARDS patients undergoing ventilation with restricted airway pressure is an interesting finding. In our investigation, it showed up as an independent risk factor for 28-day mortality and was linked to sepsis and high driving pressure readings.